2014
DOI: 10.1002/2013wr014639
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of using remotely sensed soil moisture in parameter identification of large‐scale hydrological models

Abstract: Large-scale hydrological models are nowadays mostly calibrated using observed discharge. As a result, a large part of the hydrological system, in particular the unsaturated zone, remains uncalibrated. Soil moisture observations from satellites have the potential to fill this gap. Here we evaluate the added value of remotely sensed soil moisture in calibration of large-scale hydrological models by addressing two research questions: (1) Which parameters of hydrological models can be identified by calibration wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
141
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(153 citation statements)
references
References 91 publications
8
141
1
3
Order By: Relevance
“…Operational flood forecasting models, including lumped, semi-distributed and distributed models, contain a number of parameters that can be highly conceptualized and are not directly measurable [136]. These parameters are traditionally estimated through minimizing the differences between observed and simulated streamflow in order to generate accurate and reliable future flow forecasts.…”
Section: Batch Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Operational flood forecasting models, including lumped, semi-distributed and distributed models, contain a number of parameters that can be highly conceptualized and are not directly measurable [136]. These parameters are traditionally estimated through minimizing the differences between observed and simulated streamflow in order to generate accurate and reliable future flow forecasts.…”
Section: Batch Calibrationmentioning
confidence: 99%
“…In spite of the challenge in improving streamflow prediction by calibration using soil moisture, several explorations have been carried out recently [136,[144][145][146][147] to examine the potential of improving short-term streamflow forecasting by calibrating model parameters using soil moisture remote sensing data (Table 3). A relatively early study conducted by Parajka et al [146] found that joint-calibration of a semi-distributed model using both streamflow and SAR/ERS derived soil moisture data improved the accuracy of the soil moisture predictions without degradation of the streamflow predictions.…”
Section: Batch Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, model calibration is commonly performed with watershed outlet streamflow data only. Consequently, part of the processes, specially from the unsaturated zone, can remain uncalibrated (WANDERS et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have integrated remote sensing data into the calibration of distributed hydrological models (GITHUI; SELLE; THAYALAKUMARAN, 2012;MUTHUWATTA;BOOIJ;RIENTJES, 2009) obtaining streamflow prediction performance improvement (KUNNATH-POOVAKKA et al, 2016;WANDERS et al, 2014;ZHANG et al, 2009). Rajib, Merwade and Yu (2016) calibrated the SWAT model using streamflow and soil moisture simultaneously, and compared it with the conventional calibration (streamflow only).…”
Section: Introductionmentioning
confidence: 99%